Xanthine oxidase inhibitory activity of Arcangelisia flava - Fatmawati; Subandrate; Safyudin; Medina Athiah; M Fitra Romadhon; Aulia Firdha Tariza (Acta Biochimica Indonesiana, 2022)
Background: Hyperuricemia is characterized by elevated levels of uric acid in the blood, produced from its precursor's xanthine and hypoxanthine via xanthine oxidase. Arcangelisia flava, an herbal medicine containing flavonoids, may decrease uric acid levels by inhibiting the xanthine oxidase. Objective: This study was to determine the effectiveness of ethanol extracts of A. flava leaves and stems in inhibiting xanthine oxidase. Methods: The leaves and stems of A. flava were extracted using ethanol 96%. Xanthine oxidase activity was measured using UV Vis spectrophotometry and represented as IC50 value. Allopurinol was used as a positive control. Results: The IC50 value of xanthine oxidase inhibitory of ethanol extract of A. flava leaves and stems as well as allopurinol was 174.62, 30.44, 24.03 ppm. Conclusion: The stems of A. flava have the activity of lowering uric acid levels better than the leaves.